计算:(1)(-5)+(-6)-(+12)-(-7)(2) 8-3÷(- 1 3 )×(-3) (3) - 1 4 -(-6 1
计算:(1)(-5)+(-6)-(+12)-(-7)(2)8-3÷(-13)×(-3)(3)-14-(-612)×413+(-2)3(4)[2-5×(-12)2]÷(-1...
计算:(1)(-5)+(-6)-(+12)-(-7)(2) 8-3÷(- 1 3 )×(-3) (3) - 1 4 -(-6 1 2 )× 4 13 +(-2 ) 3 (4) [2-5× (- 1 2 ) 2 ]÷(- 1 4 ) (5)(-5)×|-8|-|-3+1|-(-2)(6) (- 11 12 + 2 3 - 14 15 )×(-60) .
展开
哲宇丶0512
2015-01-23
·
超过62用户采纳过TA的回答
知道答主
回答量:123
采纳率:0%
帮助的人:59.4万
关注
(1)原式=-5-6-12+7=-23+7=-16;
(2)原式=8-3×3×3=8-27=-19;
(3)原式=-1+ × -8=-1+2-8=-7;
(4)原式=(2- )÷(- )= ÷(- )=-3;
(5)原式=-5×8-2+2=-40;
(6)原式= ×60- ×60+ ×60=55-40+56=71. |
收起
为你推荐: